The Natural Environment of Physical Activity and Perceived Stress: The Mediating Role of Specific Recovery Experiences - Schmid, Julia; Imbach, Lars; Klaperski, Sandra; Sudeck, Gorden (Frontiers in Sports and Active Living, 2021)
Objective: The purpose of this study was to investigate a potential psychological mechanism of green exercise on perceived stress. More precisely, it was analyzed whether the relationship between the natural environment of physical activity and perceived stress was mediated by recovery experiences, namely by psychological detachment and relaxation. An ecological momentary assessment approach was used, meaning that specific recovery experiences were assessed directly in real-life situations and multiple times. Materials and methods: Thirty five women and 27 men took part in the ecological momentary assessment study over seven days (Mage = 32.30 years, SD = 10.23, 53% had a degree from a university or a university of applied science). If participants were involved in PA lasting at least 10 min on a given day, they had to answer questionnaires on the smartphone both prior to the activity and immediately afterwards. Perceived naturalness, psychological detachment and relaxation were assessed after physical activity events, whereas perceived stress was measured before and after each physical activity event. A two-level mediation analysis was conducted. The direct and indirect effect of perceived naturalness on perceived stress after engagement in physical activity was analyzed on the within- and between-person levels. Results and conclusion: Results showed that the relaxation as a recovery experience served as mediator between perceived naturalness and perceived stress after engagement in physical activity, but only on a within-person level. This means that the more natural a given individual appraised the physical activity environment, the more relaxed he or she felt during physical activity (β = 0.322, p < 0.0005). Furthermore the more relaxed the individual was, the less stress he or she perceived after exercising (β = −0.221, p < 0.0005). The psychological detachment as a recovery experience in contrast, did not serve as mediator, neither at the within- and the between-person level. Considering the indirect effect of perceived naturalness on perceived stress and the importance of relaxation experiences, current findings suggest that research should put greater emphasis on examining the specific psychological mechanisms of green exercise to make even better use of its beneficial effects in the future.